Show Me Echo – Hepatitis C: A telemedicine mentoring program for patients with hepatitis C in underserved and rural areas in Missouri as a model in developing countries - Tahan, Veysel; Almashhrawi, Ashraf; Mutrux, Rachel; A. Ibdah, Jamal (Turkish Journal of Gastroenterology, 2015)
Abstract Project (Extension for Community Healthcare Outcomes) (ECHO) is a telemedicine case-based training model for primary care providers to treat complex diseases by mentoring academicians of universities. It was first developed by the University of New Mexico for rural and underserved areas in New Mexico. The project Show Me ECHO- Hepatitis C (HCV) is an adaptation of Project ECHO to improve healthcare and hepatitis C therapy in the entire state of Missouri, including rural and underserved areas. Show Me ECHO- HCV uses telemedicine as videoconferencing technology for the case-based learning. The medical specialists of the University of Missouri–Columbia provide training and mentoring to primary care providers working in rural and urban underserved areas to deliver the best evidence-based care for patients with hepatitis C. This type of a model is promising in the management of patients with hepatitis C in developing countries with the availability of basic internet connections and potential voluntary participants.